Pertumbuhan dan Produktivitas Daun Lamun Thalassia hemprichii (Ehrenb) Ascherson di Perairan Tanjung Benoa, Bali - Santoso, Budi; Dharma, I Gusti Bagus Sila; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 4 No 2 (2018), 2017)
Thalassia hemprichii is one of the seagrass as favorite food of two protected herbivores such as Green Turtle and Dugong. The existence of Thalassia hemprichii and knowing the growth rate becomes very important for sustainability of two herbivores. The study was conducted in Tanjung Benoa waters that covering three parts of the coast such as Samuh, Conrad and Tanjung beach in February until March 2017. Thalassia hemprichii leaves growth is observed consist of long and heavy growth (dry weight) and measured leaf age that has been observed such as young, half old and old leaves. The method that used to measure the growth of Thalassia hemprichii is pruning method and determination the research location using purposive sampling method. The aim of this research is explained the growth rate, biomass, and productivity of young leaves, old leaves of Thalassia hemprichii in Tanjung Benoa Bali. Measurement results of Thalassia hemprichii growth between age group of leaves has different young leaves faster growth if compared with the half old leaves and old leaves with average growth is 3.41mm/day indicates that the efficiency of this seagrass growth will decrease as the leaves age. The highest biomass values ??were found in older leaves if compared with young leaves and half-old leaves with average 0.205 gbk/m 2 expected because the thick and wide leaf size will produced larger leaf biomass. The highest productivity value is found in oldest leaves in each station with average 0.028 gbk/m 2 /day expected morphology and different nutrient content in each leaf tissue.